Crystal structure of the nickel(II) complex aqua-(2,6-di(pyrazin-2-yl)-4,4′-bipyridine-κ3 N,N′,N′′)-(phthalato-κ2 O,O′)nickel(II) tetrahydrate, C26H26N6O9Ni - Yu-Fang Wang; Zhang Shu-Qi (Zeitschrift für Kristallographie - New Crystal Structures)
C26H26N6O9Ni, triclinic, P 1‾ $‾{1}$ (no. 2), a = 11.2329(5) Å, b = 11.7535(5) Å, c = 12.1109(7) Å, α = 70.936(5)°, β = 75.684(4)°, γ = 63.266(4)°, V = 1340.13(13) Å3, Z = 2, R gt(F) = 0.0314, wR ref(F 2) = 0.0743, T = 290 K.